2021
DOI: 10.1007/s10040-021-02404-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of long-term groundwater overabstraction in Jordan

Abstract: In 2017, a comprehensive review of groundwater resources in Jordan was carried out for the first time since 1995. The change in groundwater levels between 1995 and 2017 was found to be dramatic: large declines have been recorded all over the country, reaching more than 100 m in some areas. The most affected areas are those with large-scale groundwater-irrigated agriculture, but areas that are only used for public water supply are also affected. The decrease of groundwater levels and saturated thickness poses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, we found that grasslands with lower AGB were also predominantly distributed in these regions, lower and decreasing water availability might be contributing to the grasslands with lower AGB were more likely to experience a reduction in AGB. Given the extensive negative impact of cropland on grasslands and the widespread expansion of oasis cropland globally (e.g., in West Asia and the Mediterranean region) (Brückner et al., 2021; Mekki et al., 2013), the investigation of Chinese oases offers valuable insights into the sustainable management of oases in other regions worldwide. The recently occurred and ongoing ecological degradation phenomena should remind decision‐makers to carefully consider environmental costs while pursuing economic development and increased food production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that grasslands with lower AGB were also predominantly distributed in these regions, lower and decreasing water availability might be contributing to the grasslands with lower AGB were more likely to experience a reduction in AGB. Given the extensive negative impact of cropland on grasslands and the widespread expansion of oasis cropland globally (e.g., in West Asia and the Mediterranean region) (Brückner et al., 2021; Mekki et al., 2013), the investigation of Chinese oases offers valuable insights into the sustainable management of oases in other regions worldwide. The recently occurred and ongoing ecological degradation phenomena should remind decision‐makers to carefully consider environmental costs while pursuing economic development and increased food production.…”
Section: Discussionmentioning
confidence: 99%
“…From school, from the student up to the stakeholder level, a variety of courses, lectures, workshops, and educational programs will help to sensitize to these topics, particularly the provision of sensible water irrigation techniques and engineering aspects, such as the effect of channel diversions and bank stabilization. Increased consciousness of water resource management, a topic of high relevance for Jordan [25,[80][81][82][83][84], will help to minimize water consumption, leading to a more climate-adapted usage of resources and reducing the pressure on the eco-systems and human settlements. Education on the occurrence of natural hazards, i.e., the reasons behind and the relation to human activity, is another important topic that should be addressed within the framework of the educational aspect.…”
Section: Education and Resilience On Water Resource Management Hazard...mentioning
confidence: 99%
“…The water recovery rate is one of the main components to improve the efficiency of any desalination plant. The recovery in desalination plants is the amount of water produced or permeated per unit time, as shown in Equation (1).…”
Section: Water and Energy Assessmentmentioning
confidence: 99%